2016
DOI: 10.1016/j.mayocp.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cardiorespiratory Fitness and All-Cause Mortality

Abstract: Objective To determine whether sex modifies the relationship between fitness and mortality. Patients and Methods We included 57,284 patients without coronary artery disease or heart failure who completed a routine treadmill exercise test between 1991 and 2009. We determined metabolic equivalents of task (METs) and linked patient records with mortality data via the Social Security Death Index. Multivariable Cox regression was used to determine the association between sex, fitness, and all-cause mortality. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 31 publications
(35 reference statements)
7
36
0
2
Order By: Relevance
“…These differences may explain the fact that women did not improve total sleep time after the intervention programme, mainly due to the differences in exercise physiology between men and women . For example, women have lower gains in muscle mass, lower cardiorespiratory fitness or lower muscle strength among others. Additionally, benefits of exercise appeared to be stronger for men than women in sleep parameters .…”
Section: Discussionmentioning
confidence: 99%
“…These differences may explain the fact that women did not improve total sleep time after the intervention programme, mainly due to the differences in exercise physiology between men and women . For example, women have lower gains in muscle mass, lower cardiorespiratory fitness or lower muscle strength among others. Additionally, benefits of exercise appeared to be stronger for men than women in sleep parameters .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, women had 17% lower  VO max 2 than men, which is comparable to an often reported sex difference in CRF of about 20% 8,11 . Lower fitness among women compared to men is commonly explained by women's smaller organ and body size and higher percentage of body fat on average and lower skeletal muscle mass 7,44 . Additional analyses with sex as an additional covariate showed that sex differences are not mediated by the anthropometric, behavioral, sociodemographic and interpersonal factors used in the fully adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…23 For example, testing exercise capacity using exercise testing with or without gas exchange unmasks gender differences in the relationship of fitness to cardiovascular risk: even though men only achieve 1.7 greater METs on average, women have the same predicted mortality as men with 2.6 greater MET capacity. 24 Despite guideline-supported recommendations and the added clinical value of measuring exercise capacity (CRF), our ETT laboratory experience and that of other institutions appear to be moving towards less use of ETT. 25 This trend may eventually lead to adverse clinical outcomes when less predictive, more costly tools are relied upon in place of ETT.…”
Section: Discussionmentioning
confidence: 99%